Solution-combustion synthesis of Na3(VO1-x)2(PO4)2F1+2x as a positive electrode material for sodium-ion batteries - Oskar Grabowski; Michal Krajewski; Magdalena Winkowska-Struzik; Andrzej Czerwinski (Communications Engineering)
Abstract Sodium-vanadium fluorophosphates (NVPF) comprise a family of highly potent positive electrode materials for sodium-ion batteries, combining high energy density due to their high operating potential and good high-rate performance provided by NASICON structure. In this study, a self-combustion approach to synthesise Na3(VO1-x)2(PO4)2F1+2x (0 ≤ x ≤ 1) is reported. The method described here is based on a citrate-nitrate combustion process. As a result of the synthesis, phase-pure NVPF with uniform morphology and average grain size of 98 nm is obtained. Moreover, the self-combustion method implemented in this study results in the acquisition of a powder with excellent performance in Na-ion systems, showing high capacity (ca. 111 mAh g−1), cyclability (ca. 94% of capacity retention), and high-rate performance (ca. 91% of capacity retention). The self-combustion technique described in this paper shows a promising approach to synthesising fluorinated polyanion compounds for Na-ion batteries.